Bronkiektasis - Marliza Marliza; Jihan Zata Lini Nurhadi (Institut Nalanda, 2023)
Bronchiectasis is a chronic disorder characterized by permanent bronchial dilatation, accompanied by an inflammatory process in the bronchial wall and surrounding lung parenchyma. Morphologically, bronchiectasis is divided into 3 types, namely cylindrical or tubular bronchiectasis characterized by airway dilatation, varicose bronchiectasis (so named because its appearance is similar to varicose veins), characterized by focal constrictive areas accompanied by airway dilatation as a result of defects in the bronchial wall, cystic or saccular bronchiectasis, characterized by progressive airway dilatation ending in large cysts, saccules, or grape-like clusters (this picture is a picture of the bronchi). The clinical presentation of bronchiectasis is highly variable, some patients have no symptoms at all or only have symptoms during exacerbations, and some patients experience symptoms every day. Sputum can vary from mucoid, mucopurulent, thick, and clay. A 3-layer sputum appearance that includes a foamy upper layer, a middle layer of mucus, and a purulent lower layer is pathognomonic, but not always found. Investigations that can be carried out are blood tests, radiology and microbiology. The management carried out was giving antibiotics, bronchopulmonary hygiene such as effective coughing exercises, postural drainage, chest physiotherapy, diluting respiratory tract secretions, administering inhaled brochodilators and corticosteroids during acute exacerbations. In addition, treatment of bronchiectasis can also be done through surgery.